Explaining the Fall of Socio-Economic Inequality on Welfare in East Java: A Household Level Analysis - Ririn Nopiah Nopiah; Humam Rosyadi Rosyadi; Abdurakhman (Kantor Perwakilan Bank Indonesia Provinsi Jawa Timur, 2020)
Poverty in East Java is complex problems multidimentional. East Java Province is one of the province that has highest number of poverty in Java Island. The condition of poverty reflects that population welfare level and suspectible to poor. The aims of this study is analysis determinan socio economics to welfare in East Java by using survei data from Indonesia Family Life Survey (IFLS 5). This study was analyzed by two approach are multiple linier regression model and ordered logistic model. The results of this study shows that micro credit, years of education, social capital, infrastructure availability and assets ownership have significant effect to welfare in East Java. Demographic factors like age and number of household also shows significant result to welfare in East Java.